Utility of Specialized Imaging for Diagnosis of Chronic Wrist Pain - Dreckmann, Stephanie C.; von Schroeder, Herbert P.; Novak, Christine B.; Baltzer, Heather L. (Journal of Wrist Surgery, 2019)
Background Patients with chronic wrist pain often undergo imaging (such as magnetic resonance imaging [MRI], computed tomography [CT], or ultrasound [US]) prior to specialist assessment.Questions Is specialized wrist imaging performed prior to expert consultation necessary? Are there demographic differences between patients who do or do not receive preconsultation imaging?Patients and Methods A total of 115 patients referred to a tertiary hand center for chronic wrist pain and assessed by a hand surgeon were included. At initial consultation, surgeons were blinded to referral information and previous imaging results. The specialist performed a history, physical examination and reviewed X-rays. They established a clinical diagnosis and whether any additional investigations were needed. Prior MRI, CT, and/or US results were then reviewed and the specialists' clinical diagnosis was compared with the blinded referral diagnosis. Preconsultation imaging was categorized as having no value for diagnosis/management, some value, or high value.Results A total of 82 patients had imaging prior to specialist referral (69 MRIs, 11 CTs, and 16 ultrasounds). The majority of additional imaging (73%) was classified as unnecessary, including 77% of the MRIs and 100% of the ultrasounds. Of all the investigations performed, two CT scans were labeled highly valuable clinical aids. Older patients and those with radial-sided pain were less likely to receive preconsultation imaging. Six patients required further imaging after consultation.Conclusion Clinical assessment and X-rays are typically sufficient for a hand specialist to diagnose and manage chronic wrist pain and few patients require additional imaging.Level of Evidence This is a Level III study.
Keywords: computed tomography; imaging; magnetic resonance imaging; ultrasound; wrist pain; diagnostic tests